Echoes of shame: a comparison of the characteristics and psychological sequelae of recalled shame experiences across the voice hearing continuum. Issue 1 (26th January 2023) - Brand, R.M.; Altman, R.; Nardelli, C.; Raffoul, M.; Matos, M.; Bortolon, C.
Abstract: Background: Voice hearing occurs across a number of psychiatric diagnoses and appears to be present on a continuum within the general population. Previous research has highlighted the potential role of past experiences of shame in proneness to voice hearing in the general population. Aims: This study aimed to extend this past research and compare people with distressing voices, people with voices but no distress, and a non-voice hearing control group, on various dimensions of shame and shame memory characteristics. Method: In a cross-sectional, online study 39 distressed voice hearers, 31 non-distressed voice hearers and 50 non-voice hearers undertook a shame memory priming task in which they were prompted to recall a memory of a shaming experience from their past. They then completed questionnaires assessing the characteristics of the recalled shame event and the psychological sequalae of this event (i.e. intrusions, hyperarousal, avoidance, the centrality of shame memories, external shame, and self-criticism). Results: The majority of recalled shame memories involved experiences such as interpersonal criticism or experiences of being devalued. Univariate analyses found no significant differences between the three groups with regard to the shame events that were recalled, but the distressed voice hearer group reported significantly more hyperarousal, intrusions, self-criticism, and external shame in relation to their experience. Conclusions: The findings suggest that voice hearers recall similar types of shame experiences to non-voice hearers, but that problematic psychological sequelae of these shame experiences (in the form of intrusive memories, hyperarousal, external shame, and self-criticism) may specifically contribute to distressing voice hearing.